Numerical Research and Open Sea Tests of a 100 kW Modified Edinburgh Duck Wave Energy Convertor - Zhang, Chao; Huang, Shuo; You, Yage; Sheng, Songwei (Frontiers in Energy Research, 2019)
This paper presents a modified wave energy device. The wave energy device retains the primitive capture shape of the famous Edinburgh Duck, but uses a new type of underwater-stabilized substrate. The hydrodynamic calculation with frequency-domain models was performed to find out the optimum wave period for the wave energy converter. The results to be presented were obtained by using the Boundary Element Method (BEM), based on linear wave theory. The characteristic function expands of velocity potential in the cylindrical coordinate system was applied to limit computational domain and improve computational speed. The hydrodynamic performance of the device was assessed. The influence of hydraulic damping coefficient was evaluated. Focus was given to the capture width ratio, motion of the device and optimal hydraulic damping coefficient. After two years of construction in the shipyard, the device was constructed and an open sea test had been finished near WanShan Island, South China Sea. During the test, the daily power generation and power curve of the device were measured. In this test, amounts of test data, experience and lessons had been achieved and will be summed up and presented in the paper.